Benthic response to the strong Silurian climatic fluctuations—implications from Gotland (Sweden) - Claußen, Anna Lene; Munnecke, Axel (Facies, 2024)
Climatically the Silurian was a most unstable period, as it is shows several strong δ13C excursions, with the Lau excursion being the strongest short-lived positive δ13C excursion of the entire Phanerozoic. The causes of these excursions remain a topic of debate. In order to determine how benthic communities responded to these climatic perturbations, a microfacies analysis of carbonate rocks from the Silurian period (Late Telychian to the uppermost Ludfordian) of Gotland was conducted. The development of reefs was significantly enhanced during periods characterized by carbon isotope excursions, compared to time intervals without. In periods of elevated δ13C values (≥ 3 ‰) the abundance of bryozoans and microbes increases, and in some areas, they form reefs (bryostromatolites), while corals and stromatoporoids were the main reef builders in periods of lower isotope ratios (0–3 ‰). Furthermore, a significant increase of phosphatic components, gypsum pseudomorphs and the microproblematicum Palaeomicrocodium is observed in times of increased isotope ratios. A model is proposed that explains the changes in the benthic communities over time. It is based on previously published models and explains the geochemical processes from coastal areas to the open ocean. Changes are assumed from a humid climate in times without isotope excursions to an arid climate in times of isotope excursions. It emphasizes processes that may have led to the strong δ13C shifts during the Silurian period, and includes the phosphorus cycle in sea water as an important factor in the development of the benthic communities.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Bryostromatolites; Bryozoa; Isotope excursion; Phosphorus cycle; Reef development

Bryozoan-rich stromatolites (bryostromatolites) from the Silurian of Gotland and their relation to climate-related perturbations of the global carbon cycle - Claußen, Anna Lene; Munnecke, Axel; Ernst, Andrej (Sedimentology, 2021)
Bryozoan–stromatolite associations (bryostromatolites) formed conspicuous reef structures throughout the Sheinwoodian (Wenlock) to Ludfordian (Ludlow) stratigraphy on Gotland but have not been described so far. They are mainly composed of encrusting bryozoans forming a complex intergrowth with porostromate and spongiostromate microbes and are different from the abundant stromatoporoid–coral–algal reefs with respect to their composition. In the bryostromatolite different growth stages can be identified. The observed succession can be taken as evidence for cyclic environmental changes during reef formation. Stenohaline reef-dwelling organisms, such as echinoderms, sponges, corals and trilobites, indicate fully marine salinities. Ten localities exposing bryostromatolites were discovered. Individual bryostromatolites are small with few decimetres up to one metre in size, and occur solely in shallow marine areas. Common features of these reefs on Gotland are cauliflower-like growth, a high bryozoan diversity, a high abundance of phosphatic fossils and components such as bryozoan pearls and inarticulate phosphatic brachiopods, enhanced bioerosion, Palaeomicrocodium crusts, vadose silt and gypsum pseudomorphs. The high abundance of Palaeomicrocodium, as well as the alternation with other crust-forming contributors, suggest that it could have been formed directly at the palaeo-sea surface, probably in times of minor but high-frequency sea-level fluctuations. Vadose silt and pseudomorphs after gypsum in reef cavities indicate subaerial exposure shortly after reef growth. The high amount of phosphatic components indicates a high nutrient input, probably by dust. All bryostromatolites were formed in times of strongly elevated δ13C values. The unusual combination of sedimentological and palaeoecological features, as well as their occurrence exclusively during strong positive δ13C excursions, are evidence that the bryostromatolite development responded to climatic/oceanographic changes, which may have played an important role in reef control.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Palaeomicrocodium; phosphate; reef; stable carbon isotopes; subaerial exposure

Extreme reefs: Analyses of modern bryostromatolite ("bryolith") reefs from marginal environments in the Netherlands with comparisons to ancient analogues - Harrison, G. William M.; Claußen, Anna Lene; Schulbert, Christian; Munnecke, Axel (EGU General Assembly Conference Abstracts, 2020)

Modern brackish bryostromatolites (“bryoliths”) from Zeeland (Netherlands) - Harrison, G. William M.; Claußen, Anna Lene; Schulbert, Christian; Munnecke, Axel (Palaeobiodiversity and Palaeoenvironments, 2021)
Bryostromatolites are found in stressed environments from the Paleozoic to the Recent. They are formed by alternating layers of bryozoans and microbes. This study investigates recent bryostromatolites in brackish ponds in the Netherlands to better understand ancient analogues and the environments which hosted them. They formed a fringing reef at the site Ronde Weel and a barrier reef at Kaaskenswater. The ponds had low biodiversity with only one bivalve species, two gastropod species, one ostracod species, and three diatom species comprising most of the easily fossilizable taxa; one isopod species, one decapod species, and two polychaete species were also present. Observations of microbial layers and cementation practices indicate that an alternation of bryozoan-favouring conditions and microbe-favouring conditions is essential to forming bryostromatolites. The collected bryostromatolites only had tiny living bryozoan patches. Water tests confirmed a brackish environment but with enriched arsenic and titanium concentrations and periodic euxinia. The extreme environment explains the lack of biodiversity and may provide information about the environments in which past bryostromatolites formed.<br
Keywords: Bryozoan; Bryostromatolite; Reef

Stenolaemate bryozoans from the Graham Formation, Pennsylvanian (Virgilian) at Lost Creek Lake, Texas, USA - Ernst, Andrej; Claußen, Anna Lene; Seuß, Barbara; Wyse Jackson, Patrick (Palaeontologia Electronica, 2022)

The oldest deep-boring bivalves? Evidence from the Silurian of Gotland (Sweden) - Claußen, Anna Lene; Munnecke, Axel; Wilson, Mark A.; Oswald, Irina (Facies, 2019)
Compared to modern counterparts, bioerosion is rare in Paleozoic reefs, especially macro-bioerosion. The unique and enigmatic Silurian reefs from Gotland (Sweden), composed of bryozoans and microbial laminates, show evidence of a large amount of bioerosion. The samples contain Trypanites trace fossils, as well as a large number of undescribed macroborings. Small articulated bivalve shells are preserved in some of these macroborings, identified from thin-sections. Three-dimensional images from micro-computed tomography (microCT) reveal an additional bivalve, which is occupying a bioerosion trace. This specimen is possibly contained in a different boring that can be classified as possibly clavate-shaped. Furthermore, evidence of nestling, such as a subsequent modification of the ichnofossils, the presence of bivalves that are much smaller than the trace, or the presence of additional specimens, is missing; therefore, it is most likely that the bivalves made the borings. This is evidence for the existence of deep-boring bivalves in the Silurian.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Bioerosion; Bryozoans; Endolithic bivalves; Paleozoic; Reefs; Tofta Formation

The Silurian transgression of a palaeo-shoreline: the area between Old Radnor and Presteigne, Welsh Borderlands - Ray, David C.; Jarochowska, Emilia; Hughes, Helen E.; Claußen, Anna Lene; Tingley, Arthur C.; Moseley, John; Bremer, Oskar (Lithosphere, 2021)
Quarries between Old Radnor and Presteigne, Welsh Borderlands, expose a Silurian nearshore succession, which onlaps a rocky palaeotopography of Neoproterozoic basement that had been uplifted along the Church Stretton Fault Zone. The succession documents the Aeronian to Sheinwoodian transgression of an island or islands, with the following sequence of events: deposition of shallow-marine sandstones (Folly Sandstone Formation); regional uplift; the preservation of a rocky-shoreline and associated deposits (Dolyhir Rudite Member); deposition of limestones characterised by a profusion of coralline algae and the abundant remains of reefs (Dolyhir and Nash Scar Limestone Formation); and finally the deposition of trilobitic silty-mudstones (basal Coalbrookdale Formation). Facies analysis, carbon isotope (δ13Ccarb) values, sequence stratigraphy and collections of bryozoans, conodonts, thelodonts and trilobites, have been used here as a means of refining our stratigraphic understanding of this unique succession. The revised stratigraphy demonstrates many similarities with the adjoining Midland Platform and the wider Silurian world. Notable features include the globally recognised early Sheinwoodian carbon isotope excursion, and sea-level changes of regional and global extent. As one of the best examples of its kind, the palaeo-shoreline and nearshore succession of Old Radnor and Presteigne acts as a depositional model for ancient rocky shores worldwid